Microbial Content Test on Sliced Papaya in Area of Universitas Sumatera Utara - Lubis, Nenni Dwi Aprianti; Amelia, Sri; Balatif, Ridwan (Journal of Saintech Transfer, 2020)
Papaya is a fruit that is often consumed in Indonesia and has increased consumption from 2015-2016 based on SUSENAS 2016. Papaya has high water content (85-90%) and the pH is near neutral. This makes papaya vulnerable and suitable medium for the growth of pathogenic microbes. The presence of pathogenic microbes in papaya can cause health problems for those who consumed them. Objectives this study was to observe the microbial content of sliced papaya in the Universitas Sumatera Utara. Method this research was carried out by conducting laboratory tests and the results obtained in the form of a description of microbial content in papaya cut samples. The content of coliform microbes in sliced papaya was tested using the Most Probable Number (MPN) method and biochemical identification. Papaya samples were selected using total sampling method from the University of Sumatera Utara. Results A total of 14 sliced papaya samples were analysed in this study. By using the MPN test it was found that all papaya samples had a microbial threshold exceeding those determined by SNI 7388: 2009 which is below <20 / g. A total of 9 papaya samples (64.28%) contained Klebsiella sp. bacteria, 5 samples (35.72%) contained E.coli bacteria. Conclusions Bacteria found in this study were Escherichia coli and Klebsiella sp. The presence of microbial content in the sliced papaya sample that exceeds the threshold must be a concern of various parties in the surveillance of snacks being sold.